1995
DOI: 10.1002/jbm.820290411
|View full text |Cite
|
Sign up to set email alerts
|

Effect of parallel surface microgrooves and surface energy on cell growth

Abstract: To evaluate the effect of surface treatment and surface mi crotexture on cellular behavior, sm ooth and microtextured silicone substrata were produced. The microtextured sub strata possessed parallel surface grooves w ith a width and spacing of 2.0 (SilD02), 5.0 (SilDOS), and 10 [xm (SilDIO), The groove depth w as approxim ately 0.5 [xm. Subse quently, these substrata were either left untreated (NT) or treated by ultraviolet irradiation (UV), radiofrequency glow discharge treatment (RFGD), or both (UVRFGD). Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
114
2
5

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 205 publications
(128 citation statements)
references
References 36 publications
7
114
2
5
Order By: Relevance
“…Adjacent fibers trapping cells developed contact guidance similar to groove and ridge patterned surfaces. As a result, cells trapped between fibers attained similar aligned morphologies with cells on groove/ridge patterned surface (Clark et al 1990;den Braber et al 1995). Single cells between fibers with gaps of over 20 μm were not observed through three independent experiments.…”
Section: Cell Morphology On Aligned Fiber Scaffoldsmentioning
confidence: 95%
See 2 more Smart Citations
“…Adjacent fibers trapping cells developed contact guidance similar to groove and ridge patterned surfaces. As a result, cells trapped between fibers attained similar aligned morphologies with cells on groove/ridge patterned surface (Clark et al 1990;den Braber et al 1995). Single cells between fibers with gaps of over 20 μm were not observed through three independent experiments.…”
Section: Cell Morphology On Aligned Fiber Scaffoldsmentioning
confidence: 95%
“…5(h)-(k) and 7(e)-(h)). den Braber et al (1995) cultured rat dermal fibroblasts (RDF) on silicon substrates with etched parallel surface grooves of 10 μm width and spacing. They observed that the first RDF cells stretched along the grooves that were covered upon proliferation.…”
Section: Cell Morphology On Aligned Fiber Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-abraded surfaces (corresponding to the smallest cellular orientation and elongation), were used as a control. Although in vivo, ECM proteins assemble into structures on the order of 10-100nm, the, guidance cues of the structures on the order of μm are well documented [12,39,40]. In the native rat heart, elongated cardiomyocytes are tightly positioned between capillaries (7μm in diameter) that are spaced ∼20μm apart [41], thus structures on the order of 1-10μm have physiological relevance.…”
Section: Selection Of Topographical Cues Electrical Field Stimulatiomentioning
confidence: 99%
“…18 Parallel microgrooves on surfaces of various materials had been shown to promote the alignment of neuronal cells, [19][20][21][22][23][24][25] astrocytes, 26,27 as well as fibroblasts. 28,29 The preferred orientation of neuronal cells is parallel to the microgrooves. However, a few studies found perpendicular orientations.…”
Section: Introductionmentioning
confidence: 99%